Study of The Willingness to Pay Contributions of Independent National Health Insurance (JKN) Participants in Jambi - Noerdjoedianto, Dwi; Solida, Adila; Mekarisce, Arnild Augina (Universitas Teuku Umar, 2023)
Health is a long-term investment that is indispensable in supporting the success of Indonesian development. WHO has committed to developing a health system that can ensure everyone gets the health services they need without worrying about being constrained by costs, this health is known as Universal Health Coverage. One of the obligations of JKN participants was to pay monthly fees, Ability to pay and Willingness to pay greatly affected people's interest in paying monthly fees. As many as 83% of Indonesia's population had become participants of JKN, but the high number of JKN participants was not accompanied by the active participation of the participants in paying monthly fees. The number of visits to the Koni Primary Health Care had decreased over the past 3 years and based on the initial survey it was found that many JKN-KIS participants were in arrears to pay monthly fees. The purpose of this study was to determine the determinants of the willingness to pay dues (WTP) for independent JKN participants at the Koni Primary Health Care in Jambi City. This research was quantitative with a cross-sectional design. The samples were taken by purposive sampling technique with a total sample of 105 participants. The results showed that the variables associated with the willingness to pay contributions (WTP) were education level (p = 0.009), income level (p = 0.023) and ability to pay (ATP) (p = 0.038). Meanwhile, the unrelated variables were age (p = 0.110 and p = 1,000) and gender (p = 0.550). There was a relationship between education level and WTP. There was a relationship between the level of income and the willingness to pay, and there was a relationship between the ability to pay (ATP) and the willingness to pay for independent JKN participants. There was no relationship between age and willingness to pay, and there was no relationship between gender and willingness to pay independent JKN contributions.